A Study On Green Banking Practices In Banking Industry: Sri Lankan Context - Shameem, Aliyar Lebbe Mohamed Abdul; Haleem, Athambawa (The journal of contemporary issues in business and government, 2021)
The purpose of this investigation is to determine the multidisciplinary factors that impact on green banking practices in the banking industry in Sri Lanka. The study is carried out by establishing relevant variables to measure the economic factors, management support, customer pressure, competitor pressure, environmental concern and its extend of impact on practices of green banking. Data were collected from 300 staff of selected bank branches using a structured questionnaire to carry out the study. Five variables are considered for the research framework of this study which is namely, economic factors, competitor pressure, customer pressure, management support and environmental concerns which are used to measure the multidisciplinary factors and its impacts on green banking practices in Sri Lankan banking industry. Findings of the research show that economic factors, competitor pressure, management support and environmental concerns have high impacts while a moderate level of influence was noted for customer pressure on the adoption of green banking practices. Hypothesis testing shows a positive relationship between economic factors, management support, competitor pressure and environmental concerns while customer pressure did not show a positive relationship against green banking practices in Sri Lankan banks